The role of science in the Age of Denial and in times of pandemic: sustainability at the heart of the debate - Bursztyn, Marcel; Litre, Gabriela; Curi, Melissa; Saito, Carlos Hiroo (Sustainability in Debate, 2021)
The role of science in the Age of Denial and in times of pandemic: sustainability at the heart of the debate